Reinstatement of Solenoptera michelii (Chemsak, 1979) (Coleoptera: Cerambycidae: Prioninae: Solenopterini) as a valid species - Micheli, Julio A.; Micheli, Charyn J. (Zootaxa, 2006)
Solenoptera michelii (Chemsak) (Coleoptera: Cerambycidae: Prioninae) is resurrected from synonymy under S. thomae (Linnaeus). Characters and figures are presented to show differences between the two species.Solenoptera michelii (Chemsak) (Coleoptera: Cerambycidae: Prioninae) es rescatada de sinonímia bajo S. thomae (Linnaeus). Se presentan caracteres y figuras demostrando las diferencias entre las especies.